Grammatical Cohesion Found in “Venom: Let There Be Carnage” Moviescript - Zani Hernawati; Ervina C.M. Simatupang (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This research aims to analyzed the types of grammatical cohesion and analyzed the function of grammatical cohesion of speaker's utterance in Venom: "Let There be Carnage" Movie Script. Grammatical cohesion is one part of cohesive devices. Grammatical cohesion is very important to format the sense of sentences. Grammatical cohesion can be in the form of words, utterances, phrases that exist in the text to correlate one element to the other element. This study used Qualitative method to analyzed the data. Then, the data were collected from every character's utterance which contains grammatical cohesion in Venom: "Let There be Carnage" Movie Script. From the result of the analysis, it was discovered all types of grammatical cohesion. Then, the function of the grammatical cohesions are to indicate reference pronoun, addition, time order, spatial order, concession in argument, cause and effect, comparison, and contrast. They are used to join sentences together to make ideas more understandable to the reader.